Traumatic toenail wound in a Thai elephant (Elephas maximus indicus) : Toenail wound in elephant - Lynette Ong Huey; Agik Suprayogi; Aryani Sismin Satyaningtijas; Damiana Rita Ekastuti; Hera Maheshwari; Isdoni Bustaman; Koekoeh Santoso; Pudji Achmadi; Wasmen Manalu; Sattabongkoch Maneewong; Ronald Tarigan (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2024)
Elephant is Thailand’s national animal which represents three aspects: loyalty, longevity, and strength. Thai elephants are often used for deforestation and tourist activities, such as elephants, riding, and showering. This case report highlights a traumatic wound in the left foreleg nail of a showering Thai elephant. Nail wounds undergo infection and tissue necrosis. A bone fragment suspected to be part of the distal phalanges was found and confirmed by X-ray examination. However, a surgical approach is not recommended because of the high risk of sedation in elephants. Routine wound cleaning with antiseptics and topical antibiotics was performed on the traumatic wounds. The bone fragment was removed after necrosis of the surrounding tissues. The prognosis for this case was considered good based on the location and wound condition.